*This Math quiz is called 'Equations with Variables (Add and Subtract)' and it has been written by teachers to help you if you are studying the subject at middle school. Playing educational quizzes is a fabulous way to learn if you are in the 6th, 7th or 8th grade - aged 11 to 14.*

* It costs only $12.50 per month to play this quiz and over 3,500 others that help you with your school work. You can subscribe on the page at Join Us*

This quiz looks at more complex equations. Examine the following examples.

X - 4 = 8

In order to solve an equation with a variable, we need to make the expressions have the same value. Here, clearly X cannot equal 8 because 8 - 4 would be “4”. So how do we make the “X” equal “8”?

In a variable equation we must either add or subtract the known number in the unknown expression. In the above equation the unknown expression is “X - 4”. As this shows the number “4” is being subtracted from “X” we must add 4 to 4 as follows:

X - 4 + 4

*(NOTE: If 4 was being added in the first expression, then we would have to subtract 4 as follows: X + 4 - 4)*

We must then do the equal math to the known express of “8” as follows:

8 + 4

The new equation will now look as follows:

X - 4 + 4 = 8 + 4

We now add 8 + 4 = 12 and that makes the value of “X” equal 12.

12 - 4 = 8 so X = 12

1.

X + 83 = 159

242

42

66

76

2.

X + 5 = 33

38

28

27

37

X + 5 - 5 = 33 - 5

33 - 5 = 28

28 + 5 = 33

X = 28

33 - 5 = 28

28 + 5 = 33

X = 28

3.

X - 94 = 146

260

240

230

250

X - 94 + 94 = 146 + 94

146 + 94 = 240

240 - 94 = 146

X = 240

146 + 94 = 240

240 - 94 = 146

X = 240

4.

X - 132 = 0

264

132

-132

0

X - 132 + 132 = 0 + 132

0 + 132 = 132

132 - 132 = 0

X = 132

0 + 132 = 132

132 - 132 = 0

X = 132

5.

X + 13 = 54

67

31

41

27

X + 13 - 13 = 54 - 13

54 - 13 = 41

41 + 13 = 54

X = 41

54 - 13 = 41

41 + 13 = 54

X = 41

6.

X - 14 = 85

81

71

99

89

X - 14 + 14 = 85 + 14

85 + 14 = 99

99 - 14 = 85

X = 99

85 + 14 = 99

99 - 14 = 85

X = 99

7.

X - 67 = 52

119

109

99

17

X - 67 + 67 = 52 + 67

52 + 67 = 119

119 - 67 = 52

X = 119

52 + 67 = 119

119 - 67 = 52

X = 119

8.

X + 11 = 41

20

52

30

32

X + 11 - 11 = 41 - 11

41 - 11 = 30

30 + 11 = 41

X = 30

41 - 11 = 30

30 + 11 = 41

X = 30

9.

X + 24 = 39

63

5

25

15

X + 24 - 24 = 39 - 24

39 - 24 = 15

15 + 24 = 39

X = 15

39 - 24 = 15

15 + 24 = 39

X = 15

10.

X - 36 = 61

97

25

87

85

X - 36 + 36 = 61 + 36

61 + 36 = 97

97 - 36 = 61

X = 97

61 + 36 = 97

97 - 36 = 61

X = 97

159 - 83 = 76

76 + 83 = 159

X = 76